London Calls? Discrimination of European Job Seekers in the Aftermath of the Brexit Referendum - Di Stasio, Valentina; Heath, Anthony Francis (Frontiers in Sociology, 2021)
The central question in this article is whether there was greater discrimination against European applicants in the labor market in those English regions where public opinion was more strongly in favor of Brexit. Using a field experiment conducted immediately after the Brexit Referendum, we provide causal evidence that applicants with EU backgrounds faced discrimination when applying for jobs in England. On average, applicants from EU12 countries and applicants from Eastern European member states were both less likely to receive a callback from employers than were white British applicants. Furthermore, in British regions where support for Brexit was stronger, employers were more likely to discriminate against EU12 applicants. This finding, though, is driven by the more favorable treatment reserved to EU12 applicants applying for jobs in the Greater London area. Eastern Europeans, on the other hand, did not benefit from this ‘London advantage’. Administrative and legal uncertainties over the settlement status of EU nationals cannot explain these findings, as European applicants, both EU12 and Eastern Europeans, faced the same legislative framework in all British regions, including London. Rather, London appears to exhibit a cultural milieu of ‘selective cosmopolitanism’. These findings add to the still limited literature on the relationship between public opinion on immigrants (here proxied by the referendum vote) and the levels of ethnic discrimination recorded in field experiments.